PENGARUH KEDISIPLINAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TAMALATE DI KOTA MAKASSAR - Afiah Mukhtar (AkMen JURNAL ILMIAH, 2017)
The study aims to determine the effect of work discipline on employee performance at Tamalate District Office in Makassar City. This study used 30 samples (respondents). Methods of data analysis in the study using simple linear regression statistical analysis. The result of equation analysis is obtained by simple regression coefficient of Y = 10,516 0,705X. The result of the analysis method obtained correlation coefficient (r) = 0,566 and value r2 obtained is 0,320. Value t arithmetic = 3.632. The results showed that work discipline had a significant effect on employee performance at Tamalate District Office in Makassar City